The Effect of Grapevine Rootstock on the Performance of Vitis vinifera L. ( cv. Colombard) on a Relatively Saline Soil - Southey, J.M.; Jooste, J .H. (South African Journal of Enology and Viticulture, 2017)
The performance of grapevine cv. Colom bard grafted onto 25 rootstocks (1045P, 1103P, 775P, 99R, (RY 13), 99R (RY 2), UOR, 140Ru, 143-B Mgt, 101-14 Mgt, Ramsey, 13-5 EVEX, Constantia Metallica, Jacquez, Grezot 1, 216/3 Castel and US hybrids, 1-6, 3-6, 4-4, 2-1, 24-41, 24-10, 35-1-15, 16-13-23, 16-13-26and12-6-8] on relatively saline soils was investigated for six years. The highest yields were obtained with 13-5 EVEX, Ramsey, 143-B Mgt, 1045P and 140 Ru, whereas the US hybrids generally performed poorly, particularly those with Jacquez in their parentage. At this early stage in the trial a highly positive correlation·between yield and cane mass was found. Although total soluble solids concentration and pH generally declined with increasing yield and cane mass, differences in grape omposition appeared to be largely the result of differences in actual maturity.